Lockvogelangebote und Rabattschlachten: Der Bierverkauf des Lebensmitteleinzelhandels in den 1970er und 1980er Jahren - Bodden Nancy (Jahrbuch für Wirtschaftsgeschichte, 2023)
Previously undiscovered market studies show that the sale of beer as a loss-leader offer was already used as a competitive tool in food retailing in the 1970s and became an important feature of aggressive competition among retailers in the 1980s. The article illustrates the specific assortment and pricing policies in beer retailing and makes clear that increasing beer sales at low dumping prices led to profit losses for the stores.